Children's literature review. Volume 170 - Krstovic, Jelena O.; Gale Group (Detroit Gale, 2012)
Presents full-text literary criticism on writers and illustrators for children and young adults. Critical essays are selected from leading sources, including published journals, magazines, books, monographs, reviews, and scholarly papers.
Horatio Alger, Jr., 1832-1899 : American novelist and young adult novelist, biographer, and poet -- Ken Kesey, 1935-2001 : American novelist, essayist, and author of nonfiction, short stories, and children's works ; Entry presents commentary on Kesey's novel One Flew over the Cuckoo's Nest (1962) -- Ilse-Margret Vogel, 1913-2001 : Polish German-born American illustrator, memoirist, and author of picture books.
"Excerpts from reviews, criticism, and commentary on books for children and young people."
Keywords: Children's literature -- History and criticism; Children's literature -- Book reviews; Electronic books